Pengaruh Model Pembelajaran Discovery Learning Dengan Menggunakan Media Gambar Terhadap Keterampilan Menulis Puisi Pada Siswa Kelas IV SD Negeri Tombolo Kecamatan Pallangga Kabupaten Gowa - Hendra, Nurafni; Agus, M.; Pasiri, Yuddin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to determine the effect of the discovery learning model with image media on poetry writing skills in grade IV students of SD Negeri Tombolo, Pallangga District, Gowa Regency. This type of research is a pre-experiment with a One-group pretest-posttest design. Data collection uses a test instrument. Data analysis uses descriptive statistical analysis and inferential statistics. The subjects in this study were 20 grade IV students of SD Negeri Tombolo, Pallangga District, Gowa Regency. The results showed that the application of the discovery learning model using image media had an effect on poetry writing skills as seen from the comparison of pretest and posttest scores. pre-test results, the average value of student learning outcomes 59 very poor, namely 0.00%, less 20%, sufficient 60%, good 20%, and very good 0%, while the average value of the post-test results was 82.7. In addition, the t-test calculation was also obtained at 11.72. With a frequency (df) of 20 - 2 = 18, at a significance level of 0.05, ttable = 1.73 is obtained. Therefore, tcount>ttable at a significance level of 0.05. It can be concluded that the application of the discovery learning model using picture media in grade IV students of Tombolo Elementary School has an effect on poetry writing skills.